The Sports Column on National Daily Newspapers - Alp Çelik; Zeki Taş (ümit doğan üstün, 2015)
National daily newspapers aim to report detailed daily news. Sport pages of the newspapers contain sport columns and news about sport activities. The aim of this research was to investigate the sport columns appearing on sport pages of national daily newspapers published in Turkey. During the research process, nine national daily newspapers published in Turkey were reviewed for one year. The number of sport columns, publishing page, publishing space in cm. and accessibility of newspapers are ascertained. Newspaper field measurement, statistical and percentage calculations are made by Microsoft Excel. The study was completed with the transfer of the data obtained from Excel to Word as a document. According to the obtained data, regarding the news density on sport columns; Milliyet has the most news published, Cumhuriyet has the most news on front page, Haber Turk has the most space allocated and Zaman has been the most accessible newspaper.